The Development of E-Book Knowing Bryophyta Diversity to Train Digital Literacy - Diana, Novia Putri; Wisanti, Wisanti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Digital literacy is an ability to understand and use information needed by students in 21st-century education. Digital literacy can be trained using an e-book. Mosses plant are complex materials and need to be explained using multimedia so that the received information is not the wrong concept. This research aimed to produce an e-book of â€œKnowing Bryophyta Diversityâ€ to train digital literacy theoretically and empirically. This was development research referring to the Fenrich instructional model which the stages are analysis, planning, designing, development, implementation, and evaluation and revision were done at each stage. The theoretical feasibility is determined based on the validation carried out by two botanists, and one educational expert. The empirical feasibility is determined based on the readability test using a paragraph of 100 words with three repetitions and the teacher's response conducted by five high school biology teachers. The e-book is arranged based on three aspects, namely aspects of presentation, content, and language feasibility. The research instrument used validation sheets, readability sheets, and teacherâ€™s response questionnaires. This research parameter included validation, readability, and teacher's response that analyzed descriptively quantitatively. The results showed that the theoretical feasibility based on the validity reached 97,45% with a very valid category, while the empirical feasibility based on the readability that showed the e-book was suitable used for students of grade X that were at level 10, and the teacher responses reached 98,89% with a very feasible category. Thus, the e-book â€œKnowing Bryophyta Diversityâ€ expressed feasible to train digital literacy. Keywords : e-book, digital literacy, and knowing bryophyta diversity